Analisis Ekspansi Perkebunan Kelapa Sawit Terhadap Perubahan Sosial, Ekonomi Dan Lingkungan Di Wilayah Pedesaan (Kecamatan Batahan Kabupaten Mandailing Natal) - Sri Rahayu; Waizul Qarni; Rahmat Daim Harahap (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study aims to find out how the influence of the expansion of oil palm plantations has on social, economic and environmental changes in communities in several villages in Batahan District, Mandailing Natal Regency. Socio-economic in this case are education, income, health and development, while the environment is the environmental conditions in an area. This research is a descriptive qualitative research. The data used is primary data, data collection techniques using observation, interviews and documentation, and data analysis in this study is descriptive qualitative. Qualitative descriptive analysis or inductive thinking, which departs from facts or events that are empirical in nature and then examines and analyzes these findings so that they become general conclusions and generalizations with evidence of their implementation, then examines all the collected data. The results of the study show that the expansion of oil palm plantations has good social and economic impacts for the community, namely in terms of education, income, health and development. However, it has a bad impact on the environment, because it can cause environmental pollution and damage to soil and water.